Pembenihan Ikan Gabus (Channa striata) Secara Alami Pada Bak Beton di Balai Pengembangan Teknologi Perikanan Budidaya (BPTPB) Cangkringan Daerah Istimewa Yogyakarta - Kurniawan Wahyu Hidayat; DH. Guntur Prabowo; Dwi Amelia; Supanto (Faculty of Science and Technology University Ibrahimy, 2019)
Snakehead fish (Channa striata) is a member of the Channidae family, which can live in freshwater areas or rivers, brackish water, and swamps. Snakehead fish belong to the group of savage and aggressive carnivorous fish. Snakehead fish reproduce through spawning naturally in the rainy season. Natural physiological and environmental factors can be used as a signal to stimulate spawning in this type of fish. This fieldwork practice was carried out at the Center for Aquaculture Technology Development (BPTPB), this work practice used observation, interview, and documentation methods, parameters observed included fecundity, egg fertilization, hatching rate, specific growth rate, and survival rate. The results of the observation showed that it produced 10,000 eggs, a fertilization rate of 92%, a hatching rate of 94% growth rate, a specific growth rate of 15% and a survival rate of 94%.